2011
DOI: 10.1016/j.fitote.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory components from the buds of clove (Syzygium aromaticum) on melanin formation in B16 melanoma cells

Abstract: In the course to find a new whitening agent, we evaluated the methanol extract from bud of clove (Syzygium aromaticum) on melanin formation in B16 melanoma cells. Eugenol and eugenol acetate were isolated as the active compounds and showed melanin inhibition of 60% and 40% in B16 melanoma cell with less cytotoxicity at the concentration of 100 and 200 μg/mL, respectively. Furthermore, an essential oil prepared from the bud of clove, which contain eugenol and eugenol acetate as dominant components, showed melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 13 publications
2
29
0
3
Order By: Relevance
“…Additionally, the chemical structure of the sugar connected at the C-4 0 may also play an important role in the activity. Moreover, it should be noted that the opposite effect was reported that quercetin and quercetin-4 0 -O-glucoside which have the hydroxyl group at C-3 inhibited the melanin biosynthesis [77]. These results indicated that the hydroxyl group at C-3 of quercetin derivatives may be important to suppress the melaninogenesis activity, and the effect for melanin biosynthesis in B16 melanoma cells of quercetin glycosides are varied significantly by the presence or absence of hydroxyl group especially combing to C-3 or C-7 position.…”
Section: Synthesis Of Quercetin Derivatives and The Melanogenesis Stimentioning
confidence: 96%
“…Additionally, the chemical structure of the sugar connected at the C-4 0 may also play an important role in the activity. Moreover, it should be noted that the opposite effect was reported that quercetin and quercetin-4 0 -O-glucoside which have the hydroxyl group at C-3 inhibited the melanin biosynthesis [77]. These results indicated that the hydroxyl group at C-3 of quercetin derivatives may be important to suppress the melaninogenesis activity, and the effect for melanin biosynthesis in B16 melanoma cells of quercetin glycosides are varied significantly by the presence or absence of hydroxyl group especially combing to C-3 or C-7 position.…”
Section: Synthesis Of Quercetin Derivatives and The Melanogenesis Stimentioning
confidence: 96%
“…Eugenol Antiviral 7,45 ; antiúlcera 37,46 ; antidiabético 47 ; afrodisíaco 48 ; antioxidante 6,49 ; antitumoral 6,50,51 ; anestésico e anti-inflamatório ; inibidor de edemas 39,40 ; fagorrepelente 39,62 ; anti-inflamatório 39,40 ; antitumoral 39,41 ; antialérgico 39,63 …”
Section: Atividades Reportadasunclassified
“…Todavia, a p ese ça de β-cariofileno e outros compostos podem ser citotóxicos. 50 Durante o tratamento com eugenol nenhum efeito tóxico foi observado e a sobrevida dos camundongos, que desenvolveram carcinogênese cutânea de forma induzida após o tratamento, aumentou significativamente (75%), sugerindo um ótimo potencial quimiopreparativo. Segundo Pal e colaboradores 51 o eugenol tem efeito tanto na forma tópica quanto por administração via oral.…”
Section: Efeito Antitumoralunclassified
“…Cell viability was measured according to a previously reported method [19], using a micro-culture 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) technique. Cells (0.5 9 10 5 per well) were grown in 24-well plates.…”
Section: Cell Viabilitymentioning
confidence: 99%